The Effectiveness of Teachers Corrective Feedback in Enhancing Students Ability to Recount Text Writing - Wahidiyati, Irra (English Language Education Study Program, 2020)
Most junior high school students get some difficulties in recount text writing. The purpose of this research is to explain the kind of corrective feedback that is more effective for high achievers, for low achievers, and for mixed groups of high and low achievers in enhancing their ability in recount text writing and explain the interaction between corrective feedback, students prior achievement, and ability in recount text writing. The samples are eighth-graders ofSMP Agus Salim. The experiment group receives direct corrective feedback while the control group receives indirect corrective feedback. And from both groups, the researcher divides again into two groups of high and low achievers. Finally, direct feedback is more effective for mixed groups of high and low achievers. The sum of means score of the experimental group is 63.75. While the total means score of the control group is 63.50. The mean score of the high achievers that received direct corrective feedback is 62.00, while the low achievers were 65.5. And from the control group, the high achiever group mean is 66.00 while the low achiever group means is 61.00. So direct corrective feedback is better used for low achievers.